Weed suppressing ability of parthenin a sesquiterpene lactone from Parthenium hysterophorus - Batish, D.R.; Singh, H.P.; Saxena, D.B.; Kohli, R.K. (New Zealand Plant Protection, 2002)
To find alternate chemicals with novel mode of action allelochemicals which are natural plant products are being investigated This study was undertaken to explore the effect of parthenin (chemically a sesquiterpene lactone from Parthenium hysterophorus L) on two weed species viz Amaranthus viridis and Chenopodium murale In a laboratory bioassay germination seedling growth and dry weight accumulation of the weeds were significantly reduced by treating with parthenin The chlorophyll content and the respiratory activity were also significantly affected in the treated plants The study concluded that phytotoxicity of parthenin could be useful as a natural herbicide for future weed management programmes